Innovations from the “ivory tower”: Wilhelm Barthlott and the paradigm shift in surface science - Neinhuis, Christoph (Beilstein Journal of Nanotechnology, 2017)
This article is mainly about borders that have tremendous influence on our daily life, although many of them exist and act mostly unrecognized. In this article the first objective will be to address more generally the relation between university and society or industry, borders within universities, borders in thinking and the huge amount of misunderstandings and losses resulting from these obvious or hidden borders. In the second part and in more detail, the article will highlight the impact of the research conducted by Wilhelm Barthlott throughout his scientific career during which not only one border was removed, shifted or became more penetrable. Among the various fields of interest not mentioned here (e.g., systematics of Cactaceae, diversity and evolution of epiphytes, the unique natural history of isolated rocky outcrops called inselbergs, or the global distribution of biodiversity), plant surfaces and especially the tremendous diversity of minute structures on leaves, fruits, seeds and other parts of plants represent a common thread through 40 years of scientific career of Wilhelm Barthlott. Based on research that was regarded already old-fashioned in the 1970s and 1980s, systematic botany, results and knowledge were accumulated that, some 20 years later, initiated a fundamental turnover in how surfaces were recognized not only in biology, but even more evident in materials science.
Keywords: Wilhelm Barthlott; 70th birthday; self-cleaning surfaces; lotus-effect